Usefulness of sonication in the microbiological diagnosis of cardiovascular implantable electronic device infections: systematic review, meta-analysis and meta-regression - Guillermo Martín-Gutiérrez; Carlos Martín-Pérez; José Manuel Ortiz-de la Rosa; Encarnación Gutiérrez-Carretero; Arístides de Alarcón; José Antonio Lepe (BMC, 2024)
Abstract Background Multiple studies have demonstrated the utility of sonication to improve culture yield in patients with cardiovascular implantable electronic device (CIED) infections. Objective To analyze the usefulness of sonication in the microbiological diagnosis of CIED infections in comparison with traditional cultures. Methods Systematic database searches were performed to identify studies that provided enough data concerning both sensitivity and specificity of traditional (non-sonicated) and sonicated cultures from CIED samples. The diagnostic accuracy measures were obtained by three different statistical approaches: (i) The univariate model; (ii) The bivariate random; and (iii) The Bayesian bivariate hierarchical model. Heterogeneity was assessed using meta-regression. Findings Nine studies met the criteria for inclusion in the meta-analysis (1684 cultures). The summary estimates of sensitivity were higher for sonicated cultures (0.756) in comparison with non-sonicated cultures (0.446). On meta-regression, sonication of CIEDs significantly increased the sensitivity (p = 0.001) as well as the rates of false positive results (p = 0.003). The final model also showed that the studies that used a threshold for positivity were associated with lower rates of false positive results (p < 0.001). Interpretation Our results suggest that sonication improves the microbiological diagnosis of CIED infections in comparison with traditional cultures, but a standardization of processes is necessary.